2005
DOI: 10.1007/s10147-005-0524-7
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and quality of life in colorectal cancer patients

Abstract: The EF dimension of the EORTC QLQ-C30 predominantly assesses anxiety. Depression has a stronger impact on the global QL of patients than anxiety; therefore, the use of an additional instrument is recommended for the assessment of depression in outpatients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
102
5
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 44 publications
19
102
5
11
Order By: Relevance
“…However, almost a quarter of the respondents are at the age of 55-59 years old (23.0%) which is relatively a younger population age group. This result is in agreement with studies in Western countries by Braun et al (2011) in United States and Engle et al (2003) in Germany but on the other hand Tsunoda et al (2005) in Japan showed that majority (43.0%) of their respondents are more than 70 years old due to the ageing effect of the population. Even though this is not a national survey of CRC in this country, this reflects that younger generation of the population in Malaysia are acquiring CRC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, almost a quarter of the respondents are at the age of 55-59 years old (23.0%) which is relatively a younger population age group. This result is in agreement with studies in Western countries by Braun et al (2011) in United States and Engle et al (2003) in Germany but on the other hand Tsunoda et al (2005) in Japan showed that majority (43.0%) of their respondents are more than 70 years old due to the ageing effect of the population. Even though this is not a national survey of CRC in this country, this reflects that younger generation of the population in Malaysia are acquiring CRC.…”
Section: Discussionsupporting
confidence: 92%
“…The mean GHS in respondents at age 50 and above is at 79.69 (SD 21.37). In general the overall GHS in this preliminary study is comparable to other studies done in developed countries as shown in Table 2. b) Functional and Symptoms Score, respondents mean functional and symptoms score were compared with other studies (Engle et al, 2003;Tsunoda et al, 2005;Braun et al, 2011). The mean functional score in this study ranges between 79.50 (SD 26.58) to 92.17 (SD 13.71).…”
Section: Quality Of Lifementioning
confidence: 61%
“…However, the majority of the respondents were 55-59 years old (36.3%), which is a relatively younger population age group. This is in agreement with studies from Western countries, such as that by Braun et al (2011) from the USA and by Engel et al (2003) from Germany; however, Tsunoda et al (2005) from Japan showed that the majority (43.0%) of their respondents were older than 70 years due to the ageing effect of the population.…”
Section: Discussionsupporting
confidence: 92%
“…Respondents' mean functional and symptom scores were compared with other studies (Engel et al 2003, Tsunoda et al 2005, Braun et al 2011. The mean functional score in the present study ranged between 87.33 (IQR 16.71) and 95.21 (IQR 11.58).…”
Section: Functional and Symptom Scoresmentioning
confidence: 72%
“…The Hospital Anxiety and Depression Scale (HADS) is a self-administered questionnaire with the ability to detect minor psychiatric impairment. It is a screening instrument for anxiety and depression and has been validated in different settings for the general population and patients with a wide range of medical conditions (Zigmond and Snaith, 1983), including colorectal cancer (Tsunoda et al, 2005). There is a validated Arabic version of this questionnaire (El-Rufaie and Absood, 1987).…”
Section: Introductionmentioning
confidence: 99%